An Investigation of Wind Turbine Characteristics and the Wind Potential Assessment of Ankara, Turkey - Ucar, A.; Balo, F. (Taylor & Francis Inc, 2011)
In this study, wind characteristics and wind turbine characteristics were analyzed using the wind speed data collected from two different regions of Turkey during a period of 7 years between 2000 and 2006. Monthly mean wind power at heights of 10, 30, 50, and 70 m was found for two different regions of Turkey. Capacity factors and annual energy output from the wind turbines with a capacity of 850, 1,600, 2,000, and 3,000 kW were calculated. The wind turbines of capacity 3.0 MW for Ankara and Polatli stations were found to produce an energy output per year of 5.9 and 1.8 MW, respectively.
Keywords: Weibull and Rayleigh distributions; wind energy; wind turbine